Varmegraderne i og udenfor Bonderupgaards Melkekjelder, iagttagne i Sommeren 1858. - Meldahl, F. (Tidsskrift for Landøkonomi, 2018)
Varmegraderne i og udenfor Bonderupgaards Melkekjelder, iagttagne i Sommeren 1858.